EKSPLORASI SPASIAL CENDAWAN TANAH PADA SEKITAR RHIZOSFER TANAMAN JAMBU METE (Anacardium occidentale L.) DI KARANGASEM DAN BULELENG-BALI - Pratiwi, Farah Meita; Sutara, Pande Ketut (SIMBIOSIS, 2013)
Coconut is one of an important plant to fulfil human’s life needed. This study was conducted to determine the benefits of coconut plant parts. The study was conducted in some areas of Denpasar and Badung from 27 January until 4 February, 2012. The method used in this study is exploratory survey method by using a questionnaire and interviews. The results showed that the mostly used parts of the plant are fruit part of 53% (35% bungkak water, bungkak meat 12.9%, 4.7% shell) root 2.3%, 22 % stems, and leaves as many as 23%. The coconut tree is used as an upakara (31%), drugs (24%), construction (14%), consumer (13%), crafts (2%), fuel (8%), roofs (2%), broom (2%), and household items (4%). Keywords: Cocos nucifera L. etnobotany, exploration survey